Phytochemical and Pharmaceutical Characterization of Seseli L. Species From Georgia - Mariam Nersezashvili; Krystyna Skalicka-Woźniak; Dali Berashvili (Polskie Towarzystwo Farmaceutyczne, 2024)
The Apiaceae family, formerly known as Umbelliferae, is one of the largest plant families, composed of 466 genera and nearly 3800 species worldwide. According to the Royal Kew Garden, it is also one of 12 plant families with a higher than-normal percentage of medicinal species, ranking 6th with 15% of its plants counted as medicinal. Seseli species, known for their high coumarin content as well as terpenoids, flavonoids, essential oils, and more, have been extensively investigated and found to possess various pharmacological properties such as antimicrobial, antitumor, antioxidant, cytotoxic, anti-nociceptive, anti-inflammatory, etc. Some Seseli species have also been used in treating central nervous system disorders such as anxiety. From 135 species 12 are distributed in Georgia (original name of the country is Sakhartvelo), from which 3 are endemics. Despite numerous studies on the chemical composition and pharmacological properties of various Seseli species, some remain unexplored, especially those found in Georgia, where data is limited and out of date. Therefore, further extensive research is necessary to improve understanding of the pharmacological activities, chemical constituents, and efficacy of plants from the Georgian Seseli species. The presented review draws attention to Seseli species distributed in Georgia, their phytochemistry, botanical characterisation and traditional use. However, as the information on biological activity of Georgian Seseli spp. is limited, we discussed potential pharmacological properties expected based on their chemical composition, also in relation with the same species from other countries or botanical gardens.